Optimization-Based Controllers for Robotics Applications (OCRA): The Case of iCub’s Whole-Body Control - Eljaik, Jorhabib G.; Lober, Ryan; Hoarau, Antoine; Padois, Vincent (Frontiers in Robotics and AI, 2018)
OCRA stands for Optimization-based Control for Robotics Applications. It consists of a set of platform independent libraries which facilitates the development of optimization-based controllers for articulated robots. Hierarchical, weighted, and hybrid control strategies can easily be implemented using these tools. The generic interfaces provided by OCRA allow different robots to use the exact same controllers. OCRA also allows users to specify high-level objectives via tasks. These tasks provide an intuitive way of generating complex behaviors and can be specified in XML format. To illustrate the use of OCRA, an implementation of interest to this research topic for the humanoid robot iCub is presented.